Analisis Pengaruh Promo Gratis Ongkos Kirim Shopee Terhadap Keputusan Pembelian di Kalangan Mahasiswa Kota Bandung - Shinta Nuraini (International Journal Administration, Business & Organization, 2023)
There are many factors that influence a person's purchasing decision in buying a product, one of which is the free shipping promo. This study aims to determine the effect of the free shipping promo on purchasing decisions on the Shopee marketplace among college students in Bandung. Respondents came from Bandung city students who are active or have made purchases and used free shipping promos on the Shopee marketplace. This study used descriptive quantitative methods, validity and reliability tests, and data analysis using simple linear regression with a sample of 120 respondents. In this study, it was found that free shipping promos (X) had a significant and positive influence on purchasing decisions (Y) with a proportion of 30.7%. Meanwhile, 69.3% of Bandung city students' purchasing decisions were influenced by other factors not tested in this study. Keywords: Free shipping promo, purchase decision JEL Classifications: L81, M31